Perilaku Mahasiswa Terhadap Sosial Media - Arum Wahyuni Purbohastuti (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study is to determine the behavior of students towards the social media they have. Where for the previous research there were more who discussed the influence of social media on consumer behavior, but in this study examined the opposite. The samples taken in this study were active students aged 18-23 years. This research is a qualitative research by conducting in-depth interviews. The results obtained are that student behavior towards social media is still reasonable because students' mindset of the negative impact of social media is very understandable but students cannot deny that when they study they often take the time to open social media due to throwing away their boredom and habits. or to seek information for the sake of smooth learning.